The awareness of experience innovation and an application in private hospitals - (:unkn) unknown (PAKISTAN MEDICAL ASSOC, 2015)
Objective: To evaluate the perspective of private hospitals regarding experience innovation. Methods: The qualification-type study was conducted in Istanbul, Turkey, in February 2015, and comprised 17 hospitals where patients and employees were interviewed using a semi-structured consultation guide. The employees were examined regarding the meaning of innovation, awareness of experience innovation and its measurement. The patients were asked about the reason for choosing a hospital, the actual reason for arrival at the hospital and the impressions while leaving the hospital. Based on the obtained answers, experience innovation was examined. Results: Of the 87 subjects interviewed, 51(59%) were patients and 36(41%) were hospital employees. Overall, there were 61(70%) women and 26(30%) men in the age range of 21-75 years. It was observed that the tendencies of hospitals for innovation activities were high, but they confused it with novelty. Conclusions: Investments made without taking experience innovation into account do not convert into targeted results.
Keywords: Innovation of experience; Private hospital; Creativity; Novelty; FIRM